Filth and Decomposition in Prawns from Peeling Sheds Around Cochin - Thomas, Francis; Mathew, Kuruvila (Fishery Technology, 2025)
Samples of prawn meat collected from peeling sheds around Cochin were examined for filth and decomposition. These samples were found to be contaminated by house flies/house fly fragments in 7% samples, flies of the genus Drosophila in 12% samples, red ants/red ant fragments in 19% samples and head louse in 1% samples. 5-6% of the samples were found to be decomposed. It was observed that the smaller the size of the prawn, the higher the contamination by flies and ants and also decomposition.